FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU BERESIKO SEKSUAL PADA REMAJA DI SMA - Nita Tri Putri; Rahmi Sari Kasoema (Universitas Fort de Kock Bukittinggi, 2022)
This survey was conducted nationally by youth risk behavior in the United States in 2015, 41.2% of students sitting in 9-12 had already had sexual relations, 35% of students in the upper secondary school had actively done so.Indonesia expresses some youth bahavior dating that are not married as follow: 35.7% of youth ever get the partners, 38.7% ever hurry lips, and 75.6% youth ever hold hands with the couple. Beside that, the age is the most for dating is around 15-17 years around 46.15%. The objectives of this research are to see the factors related to sexual behavior for youth in privet senior high schools of Bukittingi in 2018.Type od this research is analytic descriptive by using cross sectional study approching. The population of this resaerch is all of privatte students of senior high school. The number of the population is 613 students by using proporsional stratified random sampling. The total of the sample is 100 students. Data is calculated manually and anlyzed as univariat in frequency dsitubution table and bivariat by using chi-square statistical test.The result of the reseach shows that 60% respondents have negavtice attitude, 58% respondents effects of pairs, 60% bad effects of mass media, 64% respondents have negative sexual behavior. Thera are correlation among attitude, pairs and mass media with sexual behavior with score p=0.037,0.000 and 0.030.It can be condluded that main factors influences sexual behavior for youth is pairs. It is suggested to the teacher in private senior high school bukittinggi to improve the promotion and give lesson about sexual behavior, and bad effect if follow the risk bahavior pairs and effect if do sexual behavior toward the caouple before married. Keywords : attitude, effect of pairs, mass media exposure, sexual behavior.